2017
DOI: 10.1002/htj.21318
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer analysis of plain and dimpled tubes with different spacings

Abstract: Heat transfer enhancement by modifying the surface of tubes is commonly practiced throughout the world. Grooves, dimples, flutes or corrugations are placed inside and outside the surface of tubes and channels for enhancement. In this article, a novel method for heat transfer enhancement by varying the spacing between the tubes is reported. A comparison is made between the heat transfer performance of plain tubes and dimpled tubes at different spacings. For analysis, an experimental setup is fabricated and asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Three various meshes are created for the flow domain in the pipe. [20][21][22] The results showed that the Nu number lower than 1.21% when the mesh number variations from 501,245 elements up to 3501683 elements. So, mesh 3,506,485 was selected for this investigation.…”
Section: Generation Of Mesh Domain and Grid-independent Studymentioning
confidence: 97%
“…Three various meshes are created for the flow domain in the pipe. [20][21][22] The results showed that the Nu number lower than 1.21% when the mesh number variations from 501,245 elements up to 3501683 elements. So, mesh 3,506,485 was selected for this investigation.…”
Section: Generation Of Mesh Domain and Grid-independent Studymentioning
confidence: 97%
“…To measure the thermophysical properties of MWCNT-W nanofluid the following Equations 2-5 were used. Density, dynamic viscosity, specific heat capacity and thermal conductivity required to calculate the various thermal performance parameters of MWCNT-W nanofluid these equations were used [23][24][25][26][27][28][29][30][31].…”
Section: Measurement Of Thermo Physical Propertiesmentioning
confidence: 99%
“…It was pointed out that critical Reynolds numbers are transited down to 1400 with the acceleration of roughness, and heat transfer enhancement can be raised to 30%. Afzal et al 13 reported heat transfer enhancement of plain and dimpled tubes with different spacings by an experimental study. The analysis showed that spacing plays an important role in affecting the surface temperature and heat transfer coefficient.…”
Section: Introductionmentioning
confidence: 99%